Kesiapan Sekolah Melaksanakan Intervensi Pendidikan Karakter Multistrategi di Jenjang Pendidikan Dasar (Persepektif Guru se Nusa Tenggara Barat) - Mujiburrahman; M. Faqih; Baiq Sarlita; M Najamudin (Journal of Mandalika Literature, 2024)
This study aims to measure the trend (tendency) of teacher perceptions regarding the implementation of character education strategies at the elementary education level. This study is a quantitative study with a survey method. Data collection using a questionnaire given to 60 students and teachers as respondents from 40 schools in Lombok, Sumbawa, Bima, and Dompu. The results of the study showed that teacher perceptions of school readiness to implement character education through multi-strategy interventions at the elementary education level were the lowest at 61% and the highest at 94%, which means they were ready and very ready